Desiccation tolerance and possible starvation trade-offs in larvicide resistant Culex and Aedes mosquitoes - Eleni C. Savvidou; Charalampos S. Ioannou; Lemonia Apocha; John S. Terblanche; Nikos T. Papadopoulos (iScience)
Summary: Larvicides are widely used for mosquito control, but resistance development complicates efforts. We investigated the interplay between insecticide resistance and environmental stress in Aedes albopictus, Culex pipiens pipiens, and Culex pipiens molestus. Mosquitoes were selected for resistance to diflubenzuron and Bacillus thuringiensis subsp. israelensis, acclimated at four temperatures, and subjected to desiccation and starvation assays. Desiccation and starvation survival were affected by species, sex, and thermal acclimation, but not by larvicide resistance. Larvicide resistance affected starvation survival in Ae. albopictus, which also exhibited higher thermal plasticity under both stressors. Females outlived males across all species and conditions. These findings highlight ecological consequences of larvicide resistance, as it does not compromise stress resistance and thermal plasticity, complicating mosquito control amid climate change. Trade-offs between starvation and desiccation in Ae. albopictus suggests potential mechanistic links between these traits and larvicide mode-of-action. Species-, context- and trait-specific larvicide resistance responses complicates mosquito control efforts.